2016
DOI: 10.1097/qai.0000000000000819
|View full text |Cite
|
Sign up to set email alerts
|

Partner Disclosure of PrEP Use and Undetectable Viral Load on Geosocial Networking Apps

Abstract: Background Recent advances in biomedical prevention strategies, including pre-exposure prophylaxis (PrEP) and achieving an undetectable viral load (UVL) among HIV-infected persons, show promise in curbing the rising incidence of HIV among men who have sex with men (MSM) in the United States. This mixed methods study aimed to investigate the frequency with which MSM encounter potential sex partners on geosocial networking apps who disclose biomedical prevention use, and how MSM make decisions about condom use a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
71
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 24 publications
5
71
0
1
Order By: Relevance
“…Men most affected by gender-related inequalities because of their feminine presentation may have less leverage to negotiate condom use and may thus benefit significantly from the option of taking PrEP. Studies that have begun to uncover ways in which PrEP affects sexual partnering through processes such as “biomed matching” (Newcomb, Mongrella, Weis, McMillen, & Mustanski, 2015) also need to consider the gendered dimension of sexual sorting processes.…”
Section: Discussionmentioning
confidence: 99%
“…Men most affected by gender-related inequalities because of their feminine presentation may have less leverage to negotiate condom use and may thus benefit significantly from the option of taking PrEP. Studies that have begun to uncover ways in which PrEP affects sexual partnering through processes such as “biomed matching” (Newcomb, Mongrella, Weis, McMillen, & Mustanski, 2015) also need to consider the gendered dimension of sexual sorting processes.…”
Section: Discussionmentioning
confidence: 99%
“…The iPrEx, iPrEx OLE, U.S. MSM Safety Study , and PROUD studies found no significant change in sexual risk behaviors among participants (13, 26, 29, 30) with each observing declines in risk behaviors (e.g., number of sex partners, frequency of condomless sex), potentially due to the risk reduction services and regular follow-up provided in the research context (29, 30). Despite these findings, recent PrEP implementation research has reported high rates of STIs in PrEP initiators (25), and other research with MSM has indicated intentions for condomless anal sex while taking PrEP (10, 31). …”
Section: Introductionmentioning
confidence: 97%
“…In addition, knowing one’s status—whether HIV-positive or HIV-negative—can help an individual to make informed decisions about behavioral strategies to reduce HIV transmission risks [13] such as serosorting [11–17], strategic positioning [1416, 18], selectively having only oral sex or mutual masturbation [1820], using condoms with partners who do not share the same HIV status, or “biomed-sorting” [i.e., restricting behaviors to partners who are taking HIV antiretroviral medications—either HIV-positive but have undetectable viral loads, or HIV-negative and taking pre-exposure prophylaxis (PrEP)] [21]. Researchers estimate that eight transmissions would be averted for every 100 persons newly aware of their HIV infection as a result of HIV treatment combined with reductions in risk behavior [22].…”
Section: Introductionmentioning
confidence: 99%